Pemberdayaan UMKM Melalui Digitalisasi, Media Promosi, dan Sertifikasi Halal - Zahra, Zavira Nurul; Thubazzainun, Muhammad Addin; Prayoga, Axse Subur; Firmansyah, Muhammad Rizqi; Subakti, Muhammad Baha Uddin; Mi’rojuddin, Muhammad Fahmi; Nurfitri, Yunita Rara; Rohayatun, Siti; Syecha, Aulia Himatus; Ashofa, Farisa Nuril; Ahnafiyah, Hilya Labibah Hamidah; Auna, Luluatun Nada; Nurjanah, Tria; Rohmah, Aniyatur; Ni’mah, Elok Nihayatun; Sahdiyah, Khalimatus; Surahmat, Surahmat (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2025)
The Community Service Program (KKN) of UIN Syekh Wasil Kediri in Ngino Village aims to improve the capabilities of UMKM using digitalization, media promotion, and halal certification approaches. Ngino Village has potential in agriculture and UMKM, but still faces difficulties in marketing and business legality. Using the Participatory Action Research (PAR) method, the KKN 87 team assisted UMKM in creating Shopee accounts, Instagram business accounts, marking locations on Google Maps, and creating promotional media such as business banners. In addition, assistance was also provided in the process of processing Business Identification Numbers (NIB) and halal certification through the OSS and SiHalal systems. The results of this activity show that UMKM are better prepared to compete in the digital era, have official legality, and can market their products more widely and professionally. This empowerment not only improves the technical skills of business actors but also strengthens branding and consumer trust in local products. This activity demonstrates that collaboration between students, technology, and the community can encourage the sustainable development of UMKM.